Complex explosion development in mines: Case study—2010 upper big branch mine explosion. Issue 3 (3rd September 2014) - Davis, Scott G.; Engel, Derek; van Wingerden, Kees
<x xml:space="preserve">Abstract</x> On April 5th, 2010, a methane explosion occurred within the Upper Big Branch mine south of Charleston, WV. Twenty‐nine men lost their lives as a result of a flammable concentration of methane that built up in the enclosed space and ignited, resulting in a methane explosion that transitioned into a coal dust explosion. This study used the FLACS computational fluid dynamics solver to conduct a detailed explosion analysis to evaluate the complex overpressure development throughout the mine as a result of the flammable cloud ignition. As a result of the accident investigation, unique explosion patterns were found in the mine where certain "blast indicators" within the mine shafts were deformed in such a manner that was inconsistent with the likely flow of the expanding blast wave. The FLACS analysis will analyze the explosion dynamics and shed light on the damage observations made after the blast. © 2014 American Institute of Chemical Engineers Process Saf Prog 34: 286–303, 2015